2008
DOI: 10.1186/1750-1172-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary intestinal lymphangiectasia (Waldmann's disease)

Abstract: Primary intestinal lymphangiectasia (PIL) is a rare disorder characterized by dilated intestinal lacteals resulting in lymph leakage into the small bowel lumen and responsible for protein-losing enteropathy leading to lymphopenia, hypoalbuminemia and hypogammaglobulinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
350
0
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(373 citation statements)
references
References 74 publications
8
350
0
15
Order By: Relevance
“…Interestingly, male and female rats fed the highest dose showed dilated intestinal lacteals involved in the absorption of dietary fats in the small intestine. Such dilation is indicative of lymphangiectasia, a rare disorder that can lead to edema and its related complications, including fatigue, abdominal pain, diarrhea, vitamin deficiencies, and weight loss [47]. The observation of jejunal lacteal dilation is extremely rare in rodent toxicity studies, so the no observed adverse effect level (NOAEL) of ashitaba powder was concluded to be 300 mg · kg −1 body weight [45].…”
mentioning
confidence: 99%
“…Interestingly, male and female rats fed the highest dose showed dilated intestinal lacteals involved in the absorption of dietary fats in the small intestine. Such dilation is indicative of lymphangiectasia, a rare disorder that can lead to edema and its related complications, including fatigue, abdominal pain, diarrhea, vitamin deficiencies, and weight loss [47]. The observation of jejunal lacteal dilation is extremely rare in rodent toxicity studies, so the no observed adverse effect level (NOAEL) of ashitaba powder was concluded to be 300 mg · kg −1 body weight [45].…”
mentioning
confidence: 99%
“…In such cases, videoscope enteroscopy may be used. Histopathological examination of duodenumjejunum and ileum biopsies confirm the presence of lacteal juice dilated mucosa (from moderate to severe) and submucosal lymphatic vessels with polyclonal normal plasma cells 8 .CT and MRI are helpful in rulling out many secondary forms of intestinal lymphangiectasia. CT may show dilatation of small bowel, thickening and hypervascularity of the mucosal folds with MRI confirming the hyperintensity on T1 images suggestive of protein rich fluid 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…secondary to constrictive pericarditis, intestinal lymphoma, lymphenteric fistula, Whipple's disease, Crohn's disease, sarcoidosis, intestinal tuberculosis, systemic sclerosis, radiation and/or chemotherapy with retroperitoneal fibrosis, human immunodeficiency virus-related enteropathy or the Fontan operation to treat cardiac malformations. Dilated lymphatics are located primarily in the small bowel resulting in severe leakage of lymph in to the gastrointestinal tract which translates into loss of proteins, immunoglobulins and lymphocytes 2,3 .This entity IJBR (2013) 04 (10) www.ssjournals.com first described by Waldmann in 1961, primarily affects children (generally diagnosed before 3 years of age) and young adults but may be diagnosed later in adulthood 4,5 . Since then, no more than two hundred cases have been reported 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal lymphangiectasia (IL) is a rare protein losing enteropathy caused by congenital malformation or obstruction of the intestinal lymphatic drainage system [1]. Elevated pressure in the intestinal lymphatic system causes dilatation and rupture of the lacteals, with loss of lymphatic fluid which is rich in fat and protein.…”
Section: Background and Aimsmentioning
confidence: 99%